Tu, felix Salomon, nube: Solomon’s Marriages in Early Christian and East Syrian Biblical Interpretation - Pragt, Marion (Vigiliae Christianae, 2021)
Abstract This article explores the political portrayal of Solomon’s marriages presented by three East Syrian authors. It will be shown that whereas Jewish and early Christian interpreters often pointed to desire and demonic influence to explain Solomon’s many marriages, Theodore bar Koni, Ishoʿdad of Merv and the commentators of the anonymous manuscript olim Diyarbakır 22 instead portrayed the marriages as a form of nuptial politics intended to provide peace. The article examines the role of this political motif against the background of Theodore of Mopsuestia’s views on Solomon and the Song of Songs. It will be argued that the ways in which the East Syrian authors evaluated Solomon’s marriages are related to their different attitudes to the Song. The article illustrates how Greek exegesis could be transmitted and transformed in the East Syrian tradition of scriptural interpretation.